If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = p + 3p Combine like terms: p + 3p = 4p -16 = 4p Solving -16 = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -16 + -4p = 4p + -4p Combine like terms: 4p + -4p = 0 -16 + -4p = 0 Add '16' to each side of the equation. -16 + 16 + -4p = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -4p = 0 + 16 -4p = 0 + 16 Combine like terms: 0 + 16 = 16 -4p = 16 Divide each side by '-4'. p = -4 Simplifying p = -4
| q+10.3=15 | | 7(2x-1)-3x=x-17 | | -4(2x-1)-2x-1=2 | | 2m=5.8 | | -3(6-8n)=-186 | | (3x-7)+(14x-2)= | | 7x-x=21 | | 20x-30x-20=4x-6 | | -6+(-15)= | | 6+6k-k=-14 | | 62-11(3-4x)=15 | | 7x-21=y | | 4(x-3)-18=16 | | 62-11(3-4x)=-5 | | q=3+2p | | 10(-2x-3)-4(5x+3)=38 | | r/10+4=3 | | 15n+12-8n=61 | | 7(2x+4)+3(1+x)=48 | | 113=-9x+50 | | 8c+3=19 | | 16=3(6x+2)+4(x-3) | | 4(5x+2)=7x-5 | | 29=1-4x | | 5(-16+4y)=40 | | 3(3x-4)-2=3(x-4)+34 | | M-4=-14 | | 4x^4-x^2+6x-9=0 | | 18x-6=10x+18 | | -6+(15)= | | 3x+2x+15=50 | | 7p-6=4+8p-6p |